Analisis Aktor dalam Tata Kelola Produksi Semen Beku (Sperma) Sapi Berkualitas Ekspor di Kecamatan Singosari Kabupaten Malang - Denny Ferdinand; Ruth Agnesia Sembiring (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study explains the analysis of actors in the governance of export quality frozen semen (sperm) production in Singosari District, Malang Regency. The importance of an actor analysis in the governance of export quality frozen semen (sperm) production is because it can help farmers, especially export quality cattle farmers, to improve their economy, and can improve the governance structure of good frozen semen production. The method used by researchers in this research method is a descriptive qualitative method. In presenting and describing it, researchers use Good Governance, which contains three indicators, namely government, private sector and community. This study shows that the Singosari Artificial Insemination Center (BBIB) is the most important part of the government in providing Counseling and Education. The private sector PT Berdikari United Live Stock (BULS) is involved in the implementation of artificial insemination. The government and private sector work together to help governance to increase the supply of frozen semen (sperm). And the community also has a role, especially farmers, in implementing programs from counseling or education that have been provided. From the management structure, the supply of export quality frozen semen (sperm) has developed and the supply of frozen semen (sperm) also has competency certification. The government has implemented an official mechanism for marketing and selling the supply of frozen semen (sperm) to several countries in the world well, such as in 8 countries from Asia and Africa. The government and the private sector map out livestock assistance based on the needs or urgency of livestock needs, and increase their role in managing the quality of frozen semen (sperm) in the world market.